Local Government Councils’ Performance and Public Service Delivery in Uganda Jinja District Council Score-Card Report 2011/2012 - Asimo, Naomi; Lusala, John Baptist; Kabasingwa, Lillian (ACODE Public Service Delivery and Accountability Report Series, 2013)
This is the second Local Government Score-card assessment report for Jinja District Local Government. The score-card assesses the performance of the Local Government Council, the District Chairperson, the Speaker and individual Councilors who are vested with powers and responsibilities to ensure effective governance of the respective Local Governments as stipulated in the Local Governments Act (CAP 234). The score-card is intended to build the capacity of leaders to deliver on their mandates and empower citizens to demand for accountability from elected leaders. The objective of this report therefore is to provide information and analysis based on an assessment conducted during the FY 2011/12. The report is based on a comprehensive review of existing documents which include: planning and budgeting, service delivery monitoring, and Jinja District Local Government performance reports. Qualitative analyses of minutes of standing committees and council sittings was also undertaken to inform the report particularly about the performance of the council, chairperson and individual councilors. Face-to-face interviews with the targeted leaders, interviews with key informants at service delivery points and focus group discussions further enriched the assessment process. A detailed analysis of the Jinja District budget indicates continued low generation of local revenue and hence heavy dependence on central government transfers which accounted for 95.2% of the district’s realized revenue in the FY 2011/12. Locally-generated revenue and donor contributions in this period accounted for 1.95% and 2.89% respectively. Noticeably, the overall budget allocation to Jinja District does not consider key district-specific factors like population influx. Among the key national priority programme areas, the education sector was allocated the highest portion of the budget (52.2%), while the environment and natural resources sector received the smallest allocation (0.7%). In terms of service delivery out-comes in the primary education sub-sector, 7.1%, 37.8%, 22.9%, and 14.1% of the pupils in the district passed in Divisions I, II, III, and IV respectively. Although the district saw a rise in the total number of pupils in Division U in 2011, an increase in passes of nearly 1% was realized in Division I. In the health sector, however, despite efforts having been made to recruit staff, levels of staffing were only at 57%, still leaving a staffing gap of 31% in the entire district. Under the water and sanitation sector, the water coverage level was at 67%.